Banyuwangi Bamboo Puppets from an Ethnomathematics Perspective - Mukarromah, Nur Azizah; Hariastuti, Rachmaniah Mirza (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2023)
Ethnomathematics denotes mathematical phenomena entrenched within cultural contexts. Bamboo puppetry emerges as an intriguing cultural enclave ripe for investigation, distinguished by unique material composition, crafting techniques, and character portrayal in contrast to conventional puppetry forms. An exploratory inquiry unfolded within the precincts of Gintangan village, Banyuwangi, facilitated by a selective triad of informants. Employing qualitative methodologies, data accrual entailed a blended approach integrating observational scrutiny and in-depth interviews. Insights gleaned from the investigation unveil that the craftsmanship of bamboo puppets entails a gamut of mathematical undertakings, encompassing enumeration, categorization, measurement, and strategic planning. Furthermore, the genesis of bamboo puppetry production intricately intertwines with ethnomathematical dimensions, elucidating the utilization of numerical operations, geometric principles, statistical analysis, and probability considerations. These findings portend the transformative potential to transmute into a bespoke educational resource for contextualized mathematics pedagogy, leveraging the craft of bamboo puppetry as a conduit for experiential learning.